Phytogeographic and syntaxonomic diversity of wall vegetation (Cymbalario-Parietarietea diffusae) in southeastern Europe. (4th May 2021) - Jasprica, Nenad; Škvorc, Željko; Pandža, Marija; Milović, Milenko; Purger, Dragica; Krstonošić, Daniel; Kovačić, Sanja; Sandev, Dubravka; Lasić, Anđelka; Caković, Danka; Stešević, Danijela; Anđić, Branko; et al.
Abstract: Walls represent globally distributed, locally extensive, artificial ecosystems. Wall vegetation is still poorly known in the Mediterranean and Temperate regions of southeastern Europe. The aim of this study is to classify and describe chasmophytic vegetation of walls, covering southeastern Europe from Slovenia to North Macedonia. From a total 463 phytosociological relevés, we identify and describe 12 distinct species – poor to moderately rich vegetation units using TWINSPAN evaluated by NMDS, and indicator values. The vegetation units are included within three alliances from two macroclimate regions: (1) vegetation of cool-temperate Europe of the Cymbalario-Asplenion alliance, and (2) Mediterranean vegetation of the Galio valantiae-Parietarion judaicae and Artemisio arborescentis-Capparidion spinosae alliances. The southernmost limit of the Cymbalario-Asplenion was determined in Central Bosnia. The presence of the Artemisio arborescentis-Capparidion spinosae in the eastern Adriatic is highlighted.